Case Report: Unique patterns of lymphocyte recovery post-hematopoietic stem cell transplant associated with hyperbaric oxygen therapy: A case series - Elsayed, Marwa; Abdelhakim, Haitham; Shune, Leyla; Abhyankar, Sunil; Singh, Anurag; Zhang, Da; McGuirk, Joseph; Aljitawi, Omar (Frontiers in Hematology, 2022)
The utilization of hematopoietic stem cell transplantation (HSCT) has been rapidly growing due to multiple factors, including better availability of donors and improved supportive care. Hyperbaric oxygen has been associated with improvement of hematopoietic stem cell (HSC) homing at the time of transplant through lowering erythropoietin level in preclinical studies. We studied the role of hyperbaric oxygen (HBO) in enhancement of engraftment of HSC when utilized prior to umbilical cord HSCT and autologous HSCT in 2 pilot clinical trials with excellent safety profile. In these two pilot studies we observed an uncommon phenomenon post-transplant, particularly a significant peripheral blood lymphocytosis and lymphocyte infiltration of different tissues in 3/34 of HBO-treated patients. This peripheral blood lymphocyte expansion was associated with various clinical manifestations that can be confused with infections, inflammatory conditions, or disease relapse. We hypothesize that this observation is related to different immune-reconstitution dynamics related to the use of HBO. While the incidence is ~9%, this may have implications as HBO is being investigated in larger clinical trials. This case series highlights the clinical presentation, course, outcome and potential implications of this significant rise in lymphocytes when utilizing HBO before HSCT.